2014
DOI: 10.4103/0974-2700.142765
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of local anesthesia with lidocaine in chronic opium abusers

Abstract: Context:It had been demonstrated that chronic opium abusers have lower pain thresholds compared with than non-abusers.Aims:This study aimed to compare the required dose of lidocaine, a common local anesthetic drug, with regard to the onset of anesthesia in opium abusers with that in non-abusers undergoing similar suturing of minor hand lacerations.Materials and Methods:In this study, 109 opium abusers and 91 non-abusers underwent similar suturing for hand lacerations known as digital block. We explained the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
5
0
2
Order By: Relevance
“…Lastly, the loss of LA potency was blocked by naloxone, but not naloxone methiodide. These results suggest the apparent decrease in LA potency observed in opioid tolerant patients, most clearly documented by Hashemian and colleagues 5 , may be due, at least in part, to a decrease in the potency of LA-induced peripheral nerve block.…”
Section: Discussionsupporting
confidence: 57%
“…Lastly, the loss of LA potency was blocked by naloxone, but not naloxone methiodide. These results suggest the apparent decrease in LA potency observed in opioid tolerant patients, most clearly documented by Hashemian and colleagues 5 , may be due, at least in part, to a decrease in the potency of LA-induced peripheral nerve block.…”
Section: Discussionsupporting
confidence: 57%
“…One randomized controlled trial compared the efficacy of a single subcutaneous palmar injection (introduced vertically through the distal joint line of the metacarpophalangeal joint) versus the traditional 2 injection technique and found similar results in terms of pain control and time of anesthesia onset [33]. An observational case control study found that patients with a history of opioid abuse who underwent digital block required a higher total amount of local anesthetic, and the time to anesthesia onset was longer [34]. In light of the current opioid epidemic, it is important to recognize that many of our patients who are opioid tolerant may require more anesthetic and take longer to achieve adequate anesthesia when receiving digital nerve blocks.…”
Section: Sedation and Analgesiamentioning
confidence: 99%
“…В последнее время было доказано повышение риска метастазирования и рецидивов злокачественных новообразований на фоне послеоперационного обезболивания опиоидами. Также следует отметить, что опиоиды способны снижать эффективность местных анестетиков [23,24].…”
Section: результаты исследованияunclassified